2020
DOI: 10.3390/ma13173790
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Behavior and Durability of Alkali-Activated Clay Mortars

Abstract: The need to increase the durability of clay-based materials, due to their inherent low strength and vulnerability in contact with water, led researchers to examine different options. In this paper, clay mortars were produced using four different activating solutions. Alkali hydroxides, alkali carbonates, and alkali silicates activating solutions were used. Interest is given to long term properties while their behavior to wetting–drying and freeze–thaw cycles is recorded. In total, the results of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Typical alkaline activators include hydroxides and salts of alkali metals. These are most commonly sodium hydroxide, sodium carbonate or water glass [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Typical alkaline activators include hydroxides and salts of alkali metals. These are most commonly sodium hydroxide, sodium carbonate or water glass [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of raw materials, such as fly ash, kaolinite, palm oil fuel ash, rice husk ash, shale, natural zeolite, types of sludge, lignite bottom ash, natural fibers, red mud, and clay and clay minerals (including bentonite and montmorillonite), are currently being investigated as possible AAMs. Studies have shown that concrete made from different industrial waste material can display comparable or even better mechanical and durability properties than those associated with OPC concrete [6][7][8][9][10][11][12][13][14]. According to the reports of the Intergovernmental Panel on Climate Change [3,15], the growth of world cement production increased sevenfold by 2010 compared to that in 1970, and from 2000, this growth has been increasing sharply driven by demand from the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Marsh et al assessed the performance of uncalcinated montmorillonite and illite clays and reported a large variation in the properties, with montmorillonite displaying the more promising behavior [13]. Karouzou et al investigated the long-term durability of alkali activation of soil samples with 13% clay particles, and the alkali-activated material demonstrated improved mechanical performance [14]. However, research on the utilization of low-grade clay as an alternative material for geopolymerization system is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%